DIVINE VALUES OF KALINDA’DA’ LITERATURE - Darmansyah, Darmansyah; Santalia, Indo (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This paper will elaborate on the value of divinity in kalinda'da' literature. This research is a library research, historical descriptive-analysis, namely research conducted through various literature studies related to the problem under study, namely kalinda'da'. The research approach used is historical, sociological, and anthropological. The primary data of this research is lontara Pattappingang Pambauang Mandar. Secondary data sources are in the form of kalinda'da' writings written by Mandar culturalists and historians. The data is processed by heuristic steps, source criticism, interpretation and historigraphy. The results show that kalinda'da' is one of the nation's cultural treasures in the form of Mandar language literature. Its form and characteristics have many similarities with the rhymes from Malay or with syair from Arabic. Kalinda'da' comes from the word